Statistical analysis [on] Universal Stainless Ware Manufacturing Company, Inc. - Baradas, Jennifer; Katigbak, Cristel; Lim, Angelito (Diliman, Quezon City College of Engineering, 2001)
Universal Stainless Ware Company, Inc., owned by Mr. Rosendo Chuakaw, is a manufacturing company located at Dalandanan, Valenzuela, Metro Manila. This company has been producing stainless steel such as pots, pans, chaffing dish, etc., since 1978. The study focused on the production of Crown Sauce Pan 18 (CSPN 18) since it is one of the components of Crown 7-Piece Set, which has the largest profit share among their product lines. According to the management, the majority of rejects occur in the blanking process. Through analysis, it was determined that the problem of rejection in this process is mainly due to the methods used by the worker. Since rejection in the blanking process is a Methods Engineering problem, the researchers focused instead on the next process having the second highest number of rejects, which is 1st draw. Factors affecting the number of rejects in the 1st draw were identified as speed cycle, material, and the interaction of the 2 factors. The purpose of this study is to determine which of these factors significantly affect the number of rejects in the 1st draw. General Factorial Design is used to determine this since the combination of the factors is also tested beside the main effects. It was verified that the machine speed has a significant effect on the number of reject and that the raw material and its interaction with the speed have no significant effect. Duncan's Multiplier Range Test (DMRT) is used in order to determine which of the machine speed setting would have a significant effect on the number of rejects. It showed that the use of speed cycle 3 (18 cycles/min) causes the significant effect of the speed. In order to decrease the number of rejects in the drawing process, the speed must not be set at 18 cycle/min. And since it was determined that the raw material and its interaction with the speed doesn't have a significant effect on the number of rejects, it is recommended that the company continue to import raw material from Thailand rather than from Japan since it is less costly without having a significant increase of rejections. However, the company must still consider conducting tests to measure the properties of the product such as hardness, malleability, resistance to corrosion, etc. which might have been affected by the change in the raw material used.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Stainless steel tableware -- Philippines